Cross-Border Transmission of Fiscal Shocks : The Role of Monetary Conditions - Blagrave, Patrick (IMF Working Papers; Working Paper ;, 2018)
Fiscal stimulus was widely advocated during the global crisis, a period characterized by monetary policy constrained by the effective lower bound (ELB) in many countries, in part because of expected positive spillovers. Standard New Keynesian models predict the cross-border transmission of fiscal shocks is stronger when monetary policy is constrained in recipients. However, the empirical evidence is scarce. This paper bridges this gap by looking at the impact of fiscal shocks in systemic (source) economies on output and demand components in a large group of (recipient) countries, under different monetary policy conditions. Empirical results are compared to simulations with a state-of-the-art estimated open-economy New Keynesian model. Our results corroborate model predictions, finding larger spillovers when recipients are at the ELB, driven by stronger responses of investment and consumption relative to normal times.